2008
DOI: 10.1007/s11284-008-0534-9
|View full text |Cite
|
Sign up to set email alerts
|

Difference in seasonal activity pattern between non‐native and native ants in subtropical forest of Okinawa Island, Japan

Abstract: Difference in seasonal activity pattern between non-native and native ants in subtropical forest of Okinawa Island, Japan Abstract Biological invasions by non-native tramp ants are reported throughout the world, particularly in island ecosystems. In Okinawa Island, a subtropical island in south-western Japan, many tramp ants including the invasive ant, Anoplolepis gracilipes, already occur. In this study activity patterns of the ground-foraging tramp and native ants were investigated for one year by using food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…Competition intensity can vary over time because of temporal variation in resource limitation (Schmitt & Holbrook 1986; Hoset & Steen 2007). If competing species exhibit differing competitive abilities under contrasting environmental conditions, such temporal variations may prevent competitive exclusion (Lauer & Spacie 2004; Descamps‐Julien & Gonzalez 2005; Suwabe et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Competition intensity can vary over time because of temporal variation in resource limitation (Schmitt & Holbrook 1986; Hoset & Steen 2007). If competing species exhibit differing competitive abilities under contrasting environmental conditions, such temporal variations may prevent competitive exclusion (Lauer & Spacie 2004; Descamps‐Julien & Gonzalez 2005; Suwabe et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Eguchi (2008) observed that the species seems to inhabit open lands and forest edges, and has probably expanded its range in some part as the result of human commerce. Pheidole parva was one of the most commonly collected ants in a myrmecological study of agricultural fields in Vietnam and Okinawa (Anh et al 2010; Suwabe et al 2009). A recent study of 18 structure invading pest ants of healthcare facilities in Singapore found Pheidole parva the most frequently encountered species (Man and Lee 2012).…”
Section: Species Accountsmentioning
confidence: 99%
“…Because they are small, numerous and colonial, they can rapidly colonize a new habitat. One of the most important factors limiting their distribution is climate (Roura-Pascual et al 2011;Dunn et al 2009;Sanders et al 2007;Jenkins et al 2011) because many features of their biology are temperature or humidity dependent, such as foraging (Brightwell et al 2010), oviposition rates (Abril et al 2008), survival (Walters and Mackay 2004), colony dynamics, the structure of foraging networks (Heller and Gordon 2006) and dominance over other species (Suwabe et al 2009). It is therefore crucial to assess their invasive potential under climate change.…”
Section: Introductionmentioning
confidence: 99%